2020
DOI: 10.3991/ijet.v15i22.15443
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Engagement Framework for Gamified E-Learning Platform Activities

Abstract: University students utilise e-learning resources to gain easy access to information and to make general enquiries. Such online environments offer alternatives to traditional learning, which is now considered expensive, and time-consuming with varying results. Student disengagement is reported as the main problem for higher education e-learning platforms, however, leading e-learning developers to employ Gamification to counteract this issue. A plethora of game elements are used in the gamification of e-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Gamification can be a means of engaging employees on tasks (Reeves & Read, 2009 [18]), fostering collaboration (McGonigal, 2011 [19]) or improving motivation (Zichermann & Linder, 2013 [20]). Deterding, Dixon, Khaled, and Nacke defined "gamification" as "the use of game design elements in a non-game context" [21]. In other words, gamification is a set of activities and processes to solve problems by using or applying the characteristics of game elements.…”
Section: Definition Of Digital Games and Digital Game-based Learningmentioning
confidence: 99%
“…Gamification can be a means of engaging employees on tasks (Reeves & Read, 2009 [18]), fostering collaboration (McGonigal, 2011 [19]) or improving motivation (Zichermann & Linder, 2013 [20]). Deterding, Dixon, Khaled, and Nacke defined "gamification" as "the use of game design elements in a non-game context" [21]. In other words, gamification is a set of activities and processes to solve problems by using or applying the characteristics of game elements.…”
Section: Definition Of Digital Games and Digital Game-based Learningmentioning
confidence: 99%
“…It is one of the most important educational gamification issues that how to combine the education and the game in the activities. Many reports present which game elements are suitable for educational gamification to increase user engagement in gamebased learning activities, including points, level, badges, leader board, and timers [13,15]. An educational game authoring tools are required to associate game missions with learning objectives.…”
Section: Game Authoring Environmentmentioning
confidence: 99%
“…Some tools that are used to generate the entertainment trend are games, videos or the creation of contests [64] as all of them are known to be useful for generating entertaining experiences on social networks [55], which increases participation in the social network communities of brands [45], [55], [63]. In the case of MOOCs, it has been shown that the use of games, fun content and user enjoyment of the course content are key to the success of the course [65].…”
Section: Social Media Marketingmentioning
confidence: 99%